Two antipodal PMSM and electric automobile - MA BINGQING; WU SHIXUN; QI WENMING (2017)
The utility model discloses a two antipodal PMSM and electric automobile, this two antipodal PMSM include casing (400), install electric motor rotor (300) and motor stator (500) in this casing (400), electric motor rotor includes rotor core (310) of being made by amorphous alloy material, and this rotor core has two antipodally, motor stator (500) include the stator core who is made by silicon steel material. Thus, the utility model provides a two antipodal PMSM can provide great power output with less size, be particularly useful for the driving motor of hypervelocity operation. 本实用新型公开了种两对极永磁同步电机和电动汽车，该两对极永磁同步电机包括壳体(400)、安装在该壳体(400)内的电机转子(300)和电机定子(500)，所述电机转子包括由非晶合金材料制成的转子铁芯(310)，该转子铁芯具有两对极，所述电机定子(500)包括由硅钢材料制成的定子铁芯。这样，本实用新型提供的两对极永磁同步电机能够以较小的尺寸提供较大的功率输出，尤其适用于超高速运行的驱动电机。